Assessing essential facilities for daily walking in a tropical campus - Afsar, Bijan; Mohd Yunus, Mohd. Yazid; Mohd Yusof, Mohd Johari (American-Eurasian Network for Scientific Information, 2015)
New urban life puts emphasis on developing environmental-friendly transportation which, walking and cycling have been promoted as broadly accessible mode of sustainable transportation. Recently, campus planners in University Putra Malaysia (UPM) have been tried to provide cycling and walking access and mobility without destroying campus qualities. This paper presents the influential physical-environmental determinants on encouraging walking and cycling, based on the users’ perceptions. Users’ perceptions data was obtained through a questionnaire survey which was completed by pedestrians and cyclists using the study site. Canopy was on the top of the list as an extremely important facility that should be developed and improved. Moreover, bus stop shelter has sorted in the top priority of pedestrians in terms of facility item. To design a pedestrian environment user’s community survey can help to improve planners’ perspective in providing a user friendly environment.